Writing with AI: Insights and experiences from researchers - TRAJANO, Karryl Kim Sagun (Institutional Knowledge at Singapore Management University, 2024)
This session is jointly organized with SMU Researcher Club Many researchers would agree that writing the research manuscript is one of the most time-consuming aspect in the research project. AI could certainly help speed up this process, but to what extent and at what cost?In this session, researchers from various disciplines will share how they have used AI to augment their manuscript writing and other parts of their workflow, including best practices and things to watch out for. Panellists: Dr Karryl Kim Sagun TrajanoResearch Fellow, S.Rajaratnam School of International Studies, Nanyang Technological University Dr Rick Lee Chi WaiGeneral Manager, World Scientific Publishing Heng Su LiResearch Associate for Cooling Singapore 2.0; Co-founder, SMU Researcher Club, Singapore Management University Moderated by Marc AstburyHead of Product, Jenni AI